The Impact of Iceland's Preferential Free Trade Agreements with Partners Outside the European Economic Area on Trade Flows - Eva M. Kristjánsdóttir 1983- (2013)
Iceland has made free trade arrangements that include 65 different countries. The single largest group of countries is the EU and EEA-EFTA partners through the EEA agreement, undoubtedly making the European Economic Area Iceland’s most important free trade market. In addition to the EEA, Iceland has made 26 free trade agreements with members outside the EEA. Most of Iceland’s preferential free trade agreements with partners outside the EEA are done in cooperation with the EFTA partners, Norway, Switzerland and Liechtenstein, and the relevance of these agreements for Iceland has, until now, not been studied comprehensively. The research objectives of this thesis are to examine trade statistics of trade flows between Iceland and its non-EEA free trade partners over a period of time, before and after the entry into force of an FTA, to establish if and how Iceland’s free trade agreements with partners outside the EEA have affected trade with the country in question and to draw conclusions about the actual effects of FTAs on Iceland’s bilateral trade flows with its non-EEA FTA partners. The results show that the FTAs with members outside the EEA do not seem to have increased trade flows between Iceland and the relevant partners. In several cases trade has even become less after the entry into force of an FTA, especially Iceland’s exports. In some cases imports from the partner country did increase, but there is no apparent positive overall correlation in trade flows after entry into force of the FTAs examined. The results confirm that the EEA agreement is by far Iceland’s single most important free trade arrangement and that the area is the most important market for Icelandic exporters. The lack of effectiveness of the FTAs examined can have several explanations, e.g. that companies lack awareness of the benefits provided by the agreements, the homogeneity of Icelandic exports, that the EFTA cooperation constraints Iceland in certain ways in choice of partners or that historically the European markets have been by ...